Design and Implementation of the Prevention System of Molds Growth Using Wireless Sensor Networks. (5th September 2013) - Choi, Shin-Hyeong
Abstract : Due to the advances in memory and processing capacity of embedded systems, wireless communications, and size of the devices, many researchers are growing more and more interested in wireless sensor networks (WSN). WSN have a large number of nodes with a sensor board, and wireless communication board, and have been applied to many fields. Summer is the season when much personal and property damage arises from various natural disasters such as the heat being reminiscent of subtropical climate and flooding from heavy rain due to global warming. This unusual temperature affects our lives much besides causing natural disasters. Recently, many problems have occurred with respect to hygiene and beauty of view especially due to growing of various molds in the residential environment. In the heat of summer, the damages from molds become serious due to the effect of temperature and humidity according to seasonal characteristics. In this paper, we build a wireless sensor network with some sensors such as temperature and humidity. And then we design and implement the prevention system of molds growth which can predict and prevent molds production in indoor environment.